TEACHING OF TECHNOLOGY IN SPECIAL BOARDING SCHOOLS - Usmаnоvа Mukhlisаkhаn Sоbirоvnа, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the use of work as the main pedagogical tool to reduce their disabilities while preparing students with disabilities for production is highlighted.